First reported study of daily, high dose transdermal application of oxybutynin in a humid country - Chung-Cheng Wang; Ming-Huei Lee; Yao-Chi Chuang; Yung-Shun Juan; Hsiang-Ying Lee; Wei-Yu Lin; Chun-Hou Liao; Hann-Chorng Kuo (Continence, 2022)
Objectives:: We investigated the efficacy and safety of a transdermal oxybutynin patch in treating patients with overactive bladder (OAB). Methods:: Ninety-three adult patients with OAB who were under stable treatment with antimuscarinic agents, mirabegron, or both for at least 1 month were prospectively recruited from seven hospitals in Taiwan. Patients who agreed to participate in the study stopped oral OAB medication for 2 weeks and started once-daily transdermal oxybutynin 75 mg. We evaluated the Overactive Bladder Symptom Score (OABSS), Patient Perception of Intensity of Urgency Scale (PPIUS), Patient Perception of Bladder Condition (PPBC), voiding diary, uroflowmetry, post-voiding residual urine, Global Response Assessment (GRA), and adverse events at baseline, 2 weeks, and 4 weeks. Results:: Mean patient age was 66.7 ± 14.8 years. Compared with the measurements at baseline, the GRA, OABSS, PPIUS, PPBC, urinary urgency incontinence, urgency, and frequency significantly improved after 2 and 4 weeks of treatment. At 4 weeks, 20 patients (25%) reported markedly improvement (GRA = +3), 11 (13.8%) reported moderate improvement (GRA = +2), and 28 (35%) reported mild improvement (GRA = +1). Patients with GRA ≥ 1 had a significantly less proportion of oral combination therapy compared with those with GRA < 1 (5/59, 8.5% vs 8/21, 38.1%, p < 0.01). Common adverse events included skin itching in 34 (36.6%) patients, dry mouth in 20 (21.5%), and erythema in 7 (7.5%). Conclusion:: The transdermal oxybutynin patch was effective and safe in the treatment of patients with OAB after switching from oral OAB medications.